Digital Talent Management: Adaptive Strategies in the Era of Industry 4.0 Transformation - Bambang Masudi; Rachmad Ilham; Suharto Suharto (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study explores how adaptive strategies contribute to effective digital talent management (DTM) in the context of Industry 4.0 transformation. As organizations face increasing digital disruption, strategic approaches to human resource management become essential for sustaining workforce competitiveness. Drawing on a qualitative descriptive method through systematic literature review, this research develops a conceptual framework linking adaptive strategiesmsuch as organizational flexibility, continuous learning, and hybrid work systems with successful DTM outcomes. Findings suggest that adaptive capabilities enable organizations to align their human capital with emerging technological demands, fostering innovation and long term resilience. The study provides theoretical insights into strategic HRM and dynamic capabilities, while offering practical guidance for implementing agile and digitally integrated talent systems in various industries. The implications highlight the role of learning cultures, structural reconfiguration, and remote collaboration in shaping future ready talent ecosystems in the digital era.